Türkiye’de mesleki ve teknik eğitimin gelişiminde İşkur’un rolü - Toprak, Ömer Faruk (My University, 2018)
Günümüzde her alanda çok hızlı bir değişim süreci yaşanmaktadır. Özelliklebu değişim, üretim yapısı ve istihdam üzerinde büyük dönüşümlere sebep olmaktadır.Teknolojik gelişmelerin her geçen gün üretimde daha geniş şekilde yer alması, hem yenimesleklerin doğmasına hem de mevcut mesleklerin iş tanımlarının ve yetkinliklerinindeğişmesine sebep olmaktadır. Yaşanan değişime uyum sağlayamayan bireyler işsizkalmaktadırlar. İşsizliğin azaltılması için aktif ve pasif istihdam politikalarıuygulanmaktadır. Pasif politikalar işsizliğin olumsuz etkilerini giderirken, aktifpolitikalar ise işsizliği ortadan kaldırmayı hedefler.Bu noktada aktif istihdam politikaları kapsamında uygulanan ve istihdamedilebilirliği artıran mesleki ve teknik eğitim programları ön plana çıkmaktadır.Çalışmada mesleki ve teknik eğitimin kavramsal çerçevesi çizilmiş ve Osmanlıİmparatorluğu’ndan günümüz Türkiye’sine kadar olan süreçte uygulanan meslekieğitim faaliyetleri ile aktif istihdam politikaları incelenmiştir. Bu doğrultuda Türkiye’deaktif istihdam politikalarının uygulayıcısı olan İŞKUR’un faaliyetleri ele alınmıştır.İŞKUR’un Türkiye’de mesleki ve teknik eğitimin gelişimine olan katkısı, bu yöndekiçalışmaları ve projeleri değerlendirilmiştir.

In today's world, the rapid change has been experienced in all fields. Thechange induces major transformations especially on the production structure andemployment. More widespread use of technological developments on production bytime cause both new professions to be born and change in the job descriptions of currentprofessions and theirs competences. Those who do not adopt experienced changebecomes unemployed. Active and passive employment policies are applied to decreaseemployment. While passive policies eliminate the negative effect of unemploymentunemployed, active policies aims to remove unemployment and newcomers is essentialfor both economic development and struggle with the unemployment by creation of aneffective employment market. At this point, active and passive employment policies areat he forefront.At this point, vocational and technical education programs performed withinthe scope of active employment policies and enhancing employability becomeprominent. In the study, the conceptual structure of vocational and technical educationwas dealt with and vocational education movements together with active employmentpolicies carried out a time from the Ottoman Empire to today’s Turkey were examined.In this direction, activities of İŞKUR (Turkish Job Agency) which is implementer of theiiiactive employment policies in Turkey were handled. The contribution of İŞKUR toimprovement of vocational and technical education, its the studies and projects in thisaspect were evaluated.
Keywords: Active and Passive Employment Market Policies; Aktif ve Pasif İstihdam Piyasası Politikaları Vocational and Technical Education; Employment; İnsangücü politikası; İstihdam; İşgücü piyasası; İŞKUR; İşsizlik; Labor market; Manpower policy; Mesleki eğitim; Mesleki ve teknik eğitim; Turkey; Turkish Job Agency; Türkiye; Türkye; Unemployment; Vocational and technical education; Vocational education